1984
DOI: 10.1177/019262338401200302
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation Studies on Induced and Spontaneous Nodules from B6C3F1Mouse Liver

Abstract: The present research was designed to assess the potential for progressive growth of hyperplastic, adenomatous, and carcinomatous mouse liver lesions grafted into syngeneic hosts and to determine the effect of treatment type, donor age, and metastatic potential on this parameter. Lesions were obtained from male B6/C3F1 mice fed on an open formula (NIH-007) diet or the same diet mixed with a chlorinated hydrocarbon pesticide (3,5-dichloro-(N-1,1-dimethyl-2-propyl)benzamide) (DcB). Animals were killed at 18 or 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Similar difficulties were encountered in a recent study that attempted to assess the potential of the various types of benign and malignant spontaneous hepatic nodules in B6C3F1 mice and those induced by a chlorinated hydrocarbon pesticide to grow following their transplantation into syngeneic hosts. It was concluded that morphology alone was not adequate for predicting the capacity of mouse liver nodules for autonomous growth (11).…”
Section: Some Interspecies Comparisons Of Chemical Carcinogenesismentioning
confidence: 99%
“…Similar difficulties were encountered in a recent study that attempted to assess the potential of the various types of benign and malignant spontaneous hepatic nodules in B6C3F1 mice and those induced by a chlorinated hydrocarbon pesticide to grow following their transplantation into syngeneic hosts. It was concluded that morphology alone was not adequate for predicting the capacity of mouse liver nodules for autonomous growth (11).…”
Section: Some Interspecies Comparisons Of Chemical Carcinogenesismentioning
confidence: 99%